FlocARAZI: An In‐Situ, Image‐Based Profiling Instrument for Sizing Solid and Flocculated Suspended Sediment. Issue 11 (28th October 2021) - Osborn, Ryan; Dillon, Brandon; Tran, Duc; Abolfazli, Ehsan; Dunne, Kieran B. J.; Nittrouer, Jeffrey A.; Strom, Kyle
Abstract: An inexpensive and compact underwater digital camera imaging system was developed to collect in situ high resolution images of flocculated suspended sediment at depths of up to 60 meters. The camera has a field of view of 3.7 × 2.8 mm and can resolve particles down to 5  μ m . Depending on the degree of flocculation, the system is capable of accurately sizing particles to concentrations up to 500 mg/L. The system is fast enough to allow for profiling whereby size distributions of suspended particles and flocs can be provided at multiple verticals within the water column over a relatively short amount of time (approximately 15 min for a profile of 15 m). Using output from image processing routines, methods are introduced to estimate the mass suspended sediment concentration (SSC) from the images and to separate identified particles into sand and mud floc populations. The combination of these two methods allows for the size and concentration estimates of each fraction independently. The camera and image analysis methods are used in both the laboratory and the Mississippi River for development and testing. Output from both settings are presented in this study. Plain Language Summary: Rivers carry large quantities of muddy sediment that finds its way into river beds, floodplains, lakes, reservoirs, and coastal water bodies. Scientists and engineers rely on measurements of sediment size to understand how sediment moves in a river and where it ultimately deposits. Yet, measurement of muddy sediments (sediment with particle diameters < 63  microns) has proven difficult to accomplish. Reasons for this include the small size of the sediment and the ability of small particles to stick together to form aggregates that change size depending on the conditions in the flow. For this reason, accurate measurement of the hydrodynamic size of mud cannot be achieved by sizing samples in the lab. In this study, we present an imaging system we developed to measure muddy sediment aggregates, or flocs, within natural flows. The system is relatively inexpensive, reproducible, and is capable of providing higher spatial and temporal resolution of the suspended particle sizes than any other imaging system previously developed. In the study we describe the system, test and validate it in the laboratory and field, and show how the data can be processed to provide unique information about the type and amount of sediment available in the water column. Key Points: A low‐cost underwater camera system is developed for in‐situ profile imaging of flocculated mud and other suspended particles The camera system can provide accurate measurement of suspended particle size distributions in the size range of 5–600 microns Methods are introduced to separate flocculated mud from sand in the sizing and to estimate the mass concentration of each fraction